2016
DOI: 10.18632/oncotarget.10925
|View full text |Cite
|
Sign up to set email alerts
|

A role for activated Cdc42 in glioblastoma multiforme invasion

Abstract: Cdc42 is a Rho-GTPase which plays a major role in regulating cell polarity and migration by specifying the localization of filopodia. However, the role of Cdc42 in GBM invasion has not been thoroughly investigated. We generated stable doxycycline-inducible clones expressing wild type (WT)-, constitutively active (CA)-, and dominant negative (DN)-Cdc42 in three different human glioma cell lines. Expression of CA-Cdc42 significantly increased the migration and invasive properties of malignant glioma cells compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 53 publications
7
29
0
Order By: Relevance
“…Of note, the importance of these downstream targets in GBM invasion has also been reported by different authors . For example, in GBM cell lines, loss of FAK inhibits EGF‐induced invasion , whereas Rac1 hyperactivation correlates with an elevated invasive phenotype .…”
Section: Discussionsupporting
confidence: 58%
“…Of note, the importance of these downstream targets in GBM invasion has also been reported by different authors . For example, in GBM cell lines, loss of FAK inhibits EGF‐induced invasion , whereas Rac1 hyperactivation correlates with an elevated invasive phenotype .…”
Section: Discussionsupporting
confidence: 58%
“…Of these PDZ genes, plus related genes such as small GTPases with validated functions in border cells 30 , we identified a number of conserved genes whose elevated expression correlated with decreased GBM patient survival. The results presented here, as well as recent results by others, indicate that the small GTPases Cdc42 and Rap1A are needed for the migration of both border cells and GBM CSCs 54,55,57,58 . Further work will be needed to determine the roles, if any, of the additional identified genes on GBM tumor growth, migration, and/or invasion.…”
Section: Discussionsupporting
confidence: 85%
“…Our results are consistent with recent work by Okura et al 54 , which found that knockdown of Cdc42 by siRNA decreased GBM invasion. Further, constitutively active Cdc42 reduced survival in a PDX model of glioma, while increasing the invasive capacity in sphere exit assays 54 . Thus, high Cdc42 correlates with GBM progression through increased invasion.…”
Section: Group 1 Genes) and Lower Confidence Genes (Only One Rnai Linsupporting
confidence: 94%
See 1 more Smart Citation
“…Findings regarding the role of Rac1 in glioma cell migration and invasion parallel those of Cdc42, for both, promote these two processes, bind to similar domains, are activated by common GEFs, and have the same intracellular location (at the front edge of the cell). High expression of Cdc42 in GBM is correlated with lower survival rates, since it was found to promote the highly invasive characteristics of GBM in vivo [75].…”
Section: Altered Rho-gtpasementioning
confidence: 99%